2014
DOI: 10.1111/jai.12511
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary arachidonic acid on bone in flatfish larvae: the last but not the least of the essential fatty acids

Abstract: SummaryFlatfish can provide a reliable model to study developmental disorders in bone tissues occurring during morphogenesis in response to nutritional imbalances. To date, most studies dealing with the effect of dietary essential fatty acids (EFA) on skeletogenesis in fish have focused their investigation on the role of docohexanoic (22:6nÀ3, DHA) and eicosapentaenoic (20:5n-3, EPA) acids, but only a few have focused on investigating the effects of arachidonic acid (20:4n-6, ARA) on bone during fish larval de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 80 publications
(178 reference statements)
0
7
0
Order By: Relevance
“…76 In another study, the amount of 4.5% TFA of dietary ARA during Artemia feeding period promoted proper skeletogenesis of Senegalese sole larvae. 92 The effects of dietary ARA on morphogenesis and bone in Senegalese sole have been reviewed by Boglino et al 178,179 In Atlantic cod larvae, high ARA + vitamin A (6.0% TFA + 12.0 μg g À1 ) resulted in significantly less mineralized bones in larvae of similar size (29 DPH), 85 but in zebrafish ARA enhanced turnover of the dermal skeleton, mediated by matrix metalloproteinases. 180 All these results evidenced the complicated effects of ARA on skeletogenesis depending on fish species and development stage; however, the currently available limited information precludes from any possible speculation about the biological mechanisms behind these observed phenomena.…”
Section: Functions In Eye Migration and Skeletogenesismentioning
confidence: 99%
“…76 In another study, the amount of 4.5% TFA of dietary ARA during Artemia feeding period promoted proper skeletogenesis of Senegalese sole larvae. 92 The effects of dietary ARA on morphogenesis and bone in Senegalese sole have been reviewed by Boglino et al 178,179 In Atlantic cod larvae, high ARA + vitamin A (6.0% TFA + 12.0 μg g À1 ) resulted in significantly less mineralized bones in larvae of similar size (29 DPH), 85 but in zebrafish ARA enhanced turnover of the dermal skeleton, mediated by matrix metalloproteinases. 180 All these results evidenced the complicated effects of ARA on skeletogenesis depending on fish species and development stage; however, the currently available limited information precludes from any possible speculation about the biological mechanisms behind these observed phenomena.…”
Section: Functions In Eye Migration and Skeletogenesismentioning
confidence: 99%
“…ARA can be converted to a number of compounds, including PG, thromboxanes, hydroxyeicosatetraenoic acids and LT ( 31 ) , which are very active even at low physiological concentrations and play an important role during larval development ( 7 ) . It has been demonstrated that bone development and composition at the larval stage are highly sensitive to the dietary concentration of ARA ( 54 ) . In addition, fish larvae possess a high growth rate ( 55 ) , which indicates that metabolism in this stage is active; thus, tongue sole larvae appear to be more sensitive to ARA nutrition than juvenile tongue sole are.…”
mentioning
confidence: 99%
“…Salinity and dietary ALA/LA ratio may thus influence C20 EPA, DHA and ARA synthesis with possible implications for effects on prostaglandin eicosanoid activity, a group of active hormonelike agents formed from C20 EFA. Their transitory nature fits them to an important role in modulating rapid physiological responses to stimuli while imbalances may impair skeletogenesis during early stages of larval development (Boglino et al, 2014). Successful production of pikeperch juveniles is constrained by the high incidence of skeletal anomalies (Kestemont et al, 2015) and salinity markedly affected the occurrence of skeletal abnormalities in other fishes (Lall and Lewis-McCrea, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%